CTNI-35. UPDATE ON THE FEASIBILITY STUDY OF OKN-007 IN COMBINATION WITH TEMOZOLOMIDE AND RADIATION IN NEWLY DIAGNOSED GLIOBLASTOMA. (12th November 2021) - Battiste, James; Wright, Deborah; Glenn, Chad; Dunn, Ian; Algan, Ozer; Gunter, Tyler; Zhao, Daniel; Cohoon, Andrew; Sung, Sarah; Towner, Rheal; Kim, Hyon sook
Abstract: BACKGROUND: Temozolomide (TMZ) with concurrent radiation is the traditional standard of care for newly diagnosed glioblastoma. Unfortunately, this combination has limited efficacy and resistance can render TMZ ineffective. The novel anti-cancer agent OKN-007 plus TMZ increased survival in preclinical studies. Therefore, we initiated a phase Ib/feasibility clinical trial (NCT03587038) of OKN-007 in combination with TMZ and radiation therapy (RT). We report the safety and tolerability findings of this trial in-progress. METHODS: Adults with newly-diagnosed GBM were eligible. OKN-007 was administered by IV at 60 mg/kg. There were three treatment phases: Concomitant, Pre-Maintenance, and Maintenance. In the Concomitant Phase, patients received OKN-007 three times per week (Cohort A) or five times per week (Cohort B); all patients receive TMZ at 75 mg/m 2 daily and RT at 60 Gy over 30 fractions. In the 28-day Pre-Maintenance Phase, all patients receive OKN-007 thrice weekly. In the Maintenance Phase (MP), comprising up to eighteen 28-day cycles, TMZ was dosed at 150-200 mg/m 2 on days 1-5 of each cycle for six cycles. OKN-007 was administered thrice weekly for six cycles, then twice weekly for three cycles, then once weekly for nine cycles. Each cohort was evaluated for safety with 3-6 patients followed by an expansion of cohorts if safety parameters were met. RESULTS: Three patients completed Cohort A without dose-limiting toxicity (DLT). In Cohort B, two DLT's (hematologic toxicities deemed to be related to TMZ) occurred, and this cohort was stopped. Currently, median PFS and OS have not been reached due to lack of events, but preliminary data indicate improved median PFS and OS compared to standard of care. CONCLUSIONS: The treatment plan appears safe and well-tolerated at the Cohort A combination dosing level and may increase favorable treatment outcomes suggesting that the OKN-007 warrants further study.